Physical activity promotion, human and planetary health – a conceptual framework and suggested research priorities - Abu-Omar, Karim; Chevance, Guillaume; Tcymbal, Antonina; Gelius, Peter; Messing, Sven (The Journal of Climate Change and Health, 2023)
Due to the many benefits of physical activity for human health, its promotion has established itself as an important public health topic. Global warming is influencing how and when people can be physically active, requiring adaptation measures to combat heat. At the same time, many physical activities, particularly when it comes to sports and exercise, cause carbon emissions and effect environments negatively, which opens discussions on potential ways of mitigation. This commentary lays out a framework for research priorities in the field of physical activity promotion from a perspective of planetary health. Its intent is to stimulate discussions on how research in this field can be aligned with planetary health.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Climate; Exercise; Physical activity; Planetary health; Sport; Sustainability